Integrasi HOTS dan Deep Learning dalam Desain Lembar Kerja Peserta Didik Pembelajaran Pendidikan Agama Islam : Sebuah Systematic Literature Review - Maslani Maslani; Kresna Ralfsanjani; Muhammad Iqbal; Maulana Yusup (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
21st-century Islamic Religious Education (PAI) learning is required to be oriented not only toward mastering textual material, but also toward developing Higher Order Thinking Skills (HOTS) and meaningful learning through a deep learning approach. However, the actualization of both concepts in instructional tools, particularly Student Worksheets (LKPD), still faces major challenges. Therefore, this study aims to analyze the essence of HOTS and deep learning concepts, while identifying the unique characteristics and functional forms of their integration into the design of PAI worksheets. The method employed in this study is a Systematic Literature Review (SLR) by analyzing ten relevant national and international scientific articles. The data analysis stages include comprehensive identification, rigorous selection, critical evaluation, and final synthesis of research findings. Furthermore, the results indicate that HOTS and deep learning are two complementary components that reinforce each other. HOTS functions as a cognitive target that emphasizes analysis, evaluation, and creation skills (C4–C6). Meanwhile, deep learning acts as a foundational approach that stimulates profound understanding, spiritual reflection, and meaning-making of religious substance. The characteristics of worksheets that support this integration include the use of contextual tasks, contemporary problem-solving activities, reflective questions, and connecting material with students' empirical experiences. The synthesis results prove that integrating HOTS and deep learning in PAI worksheets effectively creates a meaningful, mindful, and joyful learning atmosphere. This innovative approach contributes significantly to strengthening critical thinking and optimizing the internalization of Islamic values into students' character. Therefore, developing worksheets based on this integration is recommended as a strategic solution to support the transformation of 21st-century learning.